2015
DOI: 10.1590/1516-635x1704473-482
|View full text |Cite
|
Sign up to set email alerts
|

Managing Colllinearity in Modeling the Effect of Age in the Prediction of Egg Components of Laying Hens Using Stepwise and Ridge Regression Analysis

Abstract: The relationships between egg measurements [egg weight (EGWT), egg width (EGWD), egg shape index (EGSI), egg volume (EGV) and egg density (EGD)], and egg components [eggshell (SWT), yolk (YWT) and albumen (AWT)] were investigated in laying hens with 32, 45, and 59 weeks of age with an objective of managing multicollinearity (MC), using stepwise regression (SR) and ridge regression (RR) analyses.There were significant correlations among egg traits that led to MC problems in all eggs. Hen age influenced egg char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
4
2
0
Order By: Relevance
“…The coefficients of phenotypic correlations between the internal and external egg quality traits considered are shown in Table 4. A significant positive correlation (p < 0.01) was found between the egg weight and both the yolk weight (0.60) and albumen weight (0.91), which is consistent with the results of most studies (Suk & Park, 2001;Wolanski et al, 2007;Moula et al, 2010;Debnath & Ghosh, 2015;Shafey et al, 2015;Kgwatalala et al, 2016;Molnár et al, 2016;Ahmadu et al, 2018). Furthermore, the egg weight was found negatively correlated (p < 0.05) with the yolk ratio (-0.20) and positively correlated with the albumen ratio (0.25), which is also consistent with the results of a number of studies (Olawumi & Ogunlade, 2008;Moula et al, 2010;Debnath & Ghosh, 2015;Shafey et al, 2015;Inca et al, 2020).…”
Section: Phenotypic Correlations Between the External And Internal Eg...supporting
confidence: 87%
See 3 more Smart Citations
“…The coefficients of phenotypic correlations between the internal and external egg quality traits considered are shown in Table 4. A significant positive correlation (p < 0.01) was found between the egg weight and both the yolk weight (0.60) and albumen weight (0.91), which is consistent with the results of most studies (Suk & Park, 2001;Wolanski et al, 2007;Moula et al, 2010;Debnath & Ghosh, 2015;Shafey et al, 2015;Kgwatalala et al, 2016;Molnár et al, 2016;Ahmadu et al, 2018). Furthermore, the egg weight was found negatively correlated (p < 0.05) with the yolk ratio (-0.20) and positively correlated with the albumen ratio (0.25), which is also consistent with the results of a number of studies (Olawumi & Ogunlade, 2008;Moula et al, 2010;Debnath & Ghosh, 2015;Shafey et al, 2015;Inca et al, 2020).…”
Section: Phenotypic Correlations Between the External And Internal Eg...supporting
confidence: 87%
“…Moreover, a positive correlation between egg weight and shell weight has also been reported in numerous studies (Suk & Park, 2001;Wolanski et al, 2007;Moula et al, 2010;Shafey et al, 2015;Molnár et al, 2016;Sirri et al, 2018;Inca et al, 2020). The established absence of significant correlation between egg weight and shape index is consistent with the results of Şekeroğlu & Altuntaş (2009), Shafey et al (2015), Kgwatalala et al (2016), and Ukwu et al (2017). The positive correlation found by Moula et al (2010) stands in contrast to the negative correlation reported by Debnath & Ghosh (2015) and Inca et al (2020).…”
Section: ____________________________________________________________...supporting
confidence: 79%
See 2 more Smart Citations
“…Shell problems tend to occur in mature birds and have been associated with increased in size and decreased in shell quality (Shafey, Hussein, Mahmoud, Abouheif, & Al-Batshan, 2015;Xiao et al, 2015). It is also known that the activity of the 25-hydroxycholecalciferol-1-hydroxylase enzyme decreases and therefore, calcium absorption (Joyner, Peddie, & Taylor, 1987;Xiao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%